Development of a Stable CHO Cell Line for High-Level Expression and Purification of Recombinant Darbepoetin Alfa - Widekdo, Dwi purno; Widodo, Nashi; Rifa'i, Muhaimin; Jatmiko, Yoga Dwi (Journal of Tropical Life Science, 2026)
Recombinant Darbepoetin alfa (DARB), an erythropoiesis-stimulating agent, is widely used in treating anemia linked to chronic kidney disease and chemotherapy. This study presents a systematic approach for developing a high-yield, stable Chinese hamster ovary (CHO) cell line capable of producing recombinant DARB. A codon-optimized gene construct under dual CMV/EF1α promoters and puromycin resistance selection was transfected into CHO cells. To isolate high-producing monoclonal populations, transfected cells were subjected to limiting dilution cloning in 96-well plates, allowing single-cell-derived colonies to expand and be individually assessed. Clone DARV IV Pool 2 Clone 2E6 demonstrated the highest and most consistent DARB expression, validated through Western blot using anti-human EPO antibodies. The culture supernatant underwent two-step clarification via centrifugation and tangential flow filtration (TFF), followed by purification using anion-exchange chromatography on a HiTrap Q HP column. Gradient elution enabled effective separation, with SDS-PAGE and Western blot confirming high purity and molecular integrity of the recombinant protein. Variability in clone expression highlighted the influence of genomic integration sites and potential epigenetic silencing, emphasizing the importance of screening and stability validation. This study demonstrates that rational vector design, antibiotic-based clone selection, and robust purification strategies can produce CHO-derived DARB suitable for large-scale production. The integrated workflow supports scalability, product consistency, and regulatory readiness for biosimilar therapeutic manufacturing